V življenju ni naključij, s pravim ključem se odpirajo novi prostori: v poklon profesorici dr. Fedori Ferlugi - Petronio (1946−2018) - Premk Bogataj, Eva (Slavia Centralis, 2020)
The article is dedicated to the late professor dr. Fedori Ferlugi - Petronio (1946−2018).
Keywords: Fedora Ferluga - Petronio; biographies; Slovenian national minorities in neighbouring countries; Slavic studies